2019
DOI: 10.1002/jemt.23273
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural morphology of dermal and oral denticles of the sharpnose sevengill shark Heptranchias perlo (Elasmobranchii: Hexanchidae), a deep‐water species

Abstract: The dermal denticles are among the unique morphological adaptations of sharks, which have been acquired throughout their long evolutionary process of more than 400 million years. Species‐specific morphological characteristics of these structures has been applied specially as tools for functional and taxonomic (family‐level) studies. Nevertheless, few studies have explored the diversity of denticle structure in different around the body and oral cavity. In the present study, we described the morphological diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Additionally, it was observed that the width of the central cusp is thinner and apparently as the individual grows it can be observed that it becomes wider, it becomes more noticeable in those of the ventral region (Figure 3 and Figure 4). Overall, the presence of a crown with three cusps and a central ridge that runs the entire length of the crown in N. cepedianus dermal denticles, seems to be a morphological character shared with other species of Hexanchidae family as Heptranchias perlo (Castro, 2011;Dillon et al, 2017), Hexanchus griseus (Castro, 2011;Rangel et al, 2019), and Hexanchus nakamurai (Castro, 2011;Ebert et al, 2013). There are several types of denticles that can fulfil different functions, which are related to hydrodynamics, resistance to rock abrasion, defence, luminescence, silent movements and even food acquisition (Raschi and Elsom, 1986;Raschi and Tabit, 1992;Smith and Heemstra, 1986;Dillon et al, 2017).…”
Section: Dermal Denticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was observed that the width of the central cusp is thinner and apparently as the individual grows it can be observed that it becomes wider, it becomes more noticeable in those of the ventral region (Figure 3 and Figure 4). Overall, the presence of a crown with three cusps and a central ridge that runs the entire length of the crown in N. cepedianus dermal denticles, seems to be a morphological character shared with other species of Hexanchidae family as Heptranchias perlo (Castro, 2011;Dillon et al, 2017), Hexanchus griseus (Castro, 2011;Rangel et al, 2019), and Hexanchus nakamurai (Castro, 2011;Ebert et al, 2013). There are several types of denticles that can fulfil different functions, which are related to hydrodynamics, resistance to rock abrasion, defence, luminescence, silent movements and even food acquisition (Raschi and Elsom, 1986;Raschi and Tabit, 1992;Smith and Heemstra, 1986;Dillon et al, 2017).…”
Section: Dermal Denticlesmentioning
confidence: 99%
“…In particular, it has been studied as shark species identification tool (Tanaka et al, 2002;Valenzuela et al, 2008;Marshall, 2011), community's shark reconstruction, especially based on fossil records (Kriwet and Benton, 2004;Kriwet et al, 2008;Dillon et al, 2017;Ferrón et al, 2019;Rangel et al, 2019) and recognition of morphological patterns associated with their ecology (Reif and Dinkelacker, 1982;Reif, 1982;Muñoz-Chápuli, 1985;Reif, 1985a;Ferrón et al, 2014;Ferón and Botella, 2017;Ferrón et al, 2018;Dillon et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The denticles found in S . guggenheim presented variation in the crown shape according to the region, suggesting that their morphology is related to ecological aspects (e.g., Dillon et al, 2017; Rangel et al, 2019). We found two predominant functional morphotypes, following the denticle's classification proposed by Dillon et al (2017).…”
Section: Discussionmentioning
confidence: 99%
“…Due to their superb preservation during the fossilization process, the denticles are commonly used as a tool in taxonomic identifications (Allentoft et al, 2012; Mello et al, 2013), and recently used in paleoecological studies to identify and reconstruct shark communities (Dillon et al, 2017, 2020). Although recent studies have assessed the morphology, taxonomy, and function of dermal denticles in active pelagic sharks, sedentary demersal species have been little studied (Ankhelyi et al, 2018; Dillon et al, 2017; Rangel, Amorim, Kfoury Jr, & Rici, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shark denticles have a tooth‐like structure with an enameloid and dentine outer layer and an inner pulp cavity. Denticles are complexly shaped with a flattened outer crown area that is connected to narrower neck that extends toward the skin and an expanded base embedded in the dermis (Ankhelyi, Wainwright, & Lauder, 2018; Castro, 2011; Díez, Soto, & Blanco, 2015; Motta, Habegger, Lang, Hueter, & Davis, 2012; Oeffner & Lauder, 2012; Rangel, Amorim, Kfoury, & Rici, 2019; Reif, 1982).…”
Section: Introductionmentioning
confidence: 99%